Annual report. - John Carter Brown Library (Providence., 1911)
In addition to the principal accessions of the year, the following reports contain also special lists: 1911/12, Printed business papers, 1766-1788; 1912/13, Manuscript maps, 1511-1781; 1919/20, Books printed, 1477-1599,"which have been added to the library in the fiscal year 1919-1920 and which do not appear in the printed catalogue."
At head of title: John Carter Brown library, Providence, Rhode Island.
Report year ends April 30, 1910/11-1914/15; June 30, 1915/16-
Report for 1960/61-1964/65 issued combined.
Reports for 1906-10, printed as a part of the Annual report of the president of the University, were not issued separately.
Mode of access: Internet.
Keywords: John Carter Brown Library